Consultation in out-of-hours practice: a clinical review of Lyme disease. (2nd December 2022) - Brydon, Sharon; MacVicar, Sonya
Abstract : In this article Sharon Brydon and Dr Sonya MacVicar highlight the importance of reaching a shared decision with the patient understanding the perceived risk and benefits of treatment In recent times, telephone triage and virtual consultation have been expedited in the out-of-hours urgent primary care setting. This brings challenges concerning gaining a comprehensive history and building a therapeutic relationship between nurse prescriber and patient. This article presents a clinical review of Lyme disease to explore consultation models and how implementing a hybrid consultation approach may support the practitioner to develop safe prescribing practices and optimise patient expectations. This review of Lyme disease management highlights the sparse, low-quality evidence available, with national guidance indicating antimicrobial treatment for those who present with an erythema migrans rash prior to laboratory testing confirmation. This reinforces the importance of reaching a shared decision with the patient understanding the perceived risk and benefits of treatment. The factors discussed include Lyme disease prevention and how the practitioner ensures safety netting in the out-of-hours setting.